Secular changes in male body height in the European part of Russia during the 20th century - Lebedeva, Lidia (Array, 2020)
Significant political and economic transformations took place on the territory of contemporary Russia in the first part of the 20th century. We hypothesized that they would have affected male growth curve negatively. To test this idea, the dataset was collected to present the graph, which illustrates the changes in male body height during the 20th century. We searched for bibliographic sources with information about body height of men and women born during the 20th century, with full description of measurement methodology, sample design and significant geographical distribution of the dataset covering more than 15 territories of the country – cities or regions. Such criteria were met only for men. We found only 8 sources that could be considered reliable in the research. The observed graph confirms positive changes in male body height on the territory of the European part of contemporary Russia: for those, who were born in 1900‘s it was 166.1 cm, in 1920s – 166.5 cm, in 1940s – 171 cm, in 1960s – 174.8 cm and in 1980s the indicator reached 176.1 cm. No significant negative changes in this indicator have been found during the studied period. The primary hypothesis that political and socio-economic transformations affect male growth curve negatively was confirmed only partly. We concluded that unfavorable political and socio-economic events (such as revolutions, World War I and World War II, purges and famines) influenced the pace of body height increase in men. While the main period of secular trend was fixed in the first decades of the 20th century in Germany, Netherlands and France, in this part of Russia it occurred later, in 1930–1960s. However, the total increase in male height was very similar for all mentioned territories (9–11 cm) during 1900–1980’s.